Vegetative cardiovascular regulation in healthy people and patients with Stage I arterial hypertension - S. R. Gilyarevsky; I. G. Andreeva; N. V. Balashova; V. P. Pronina; S. I. Fedorova; V. V. Popov (Российский кардиологический журнал)
The study included 25 men (mean age 29,24±0,76 years) with Stage I arterial hypertension (AH-I). The control group consisted of 25 healthy men (mean age 30,27±0,59 years). All groups underwent 24-hour blood pressure monitoring (BPM), echocardiography (EchoCG) with Doppler ultrasound, heart rate variability (HRV) assessment, and cholesterol fraction measurement. Analyzing the correlations between vegetative parameters, levels of cholesterol and its fractions, myocardial morphology and function, it has been demonstrated that in AH-I patients, the number and strength of correlations are higher than in healthy participants. This points to a possibility of more rigid neuro-humoral cardiovascular regulation in AH-I patients, comparing to healthy individuals.